Parásitos intestinales del tepezcuinte, gouti paca (Rodentia: Dasyproctidae) en Costa Rica - Matamoros, Yolanda (Universidad de Costa Rica, 1991)
In a sample of 23 breeding places of pacas (Agouti paca) in Costa Rica, the following parasites were found: Eimeria agoutii, Balantidium coli, Capillaria sp., Trichuris sp., Taenia sp., Strongyloides sp., and members of the superfamilies Strongyloidea and Ascaroidea.